A New Stability Criterion for Systems with Distributed Time-Varying Delays via Mixed Inequalities Method. (14th April 2020) - Tian, Jun-kang; Liu, Yan-min
Abstract : This paper is concerned with the delay-dependent stability of systems with distributed time-varying delays. The novelty relies on the use of some new inequalities which are less conservative than some existing inequalities. A less conservative stability criterion is obtained by constructing some new augmented Lyapunov–Krasovskii functionals, which are given in terms of linear matrix inequalities. The effectiveness of the presented criterion is demonstrated by two numerical examples.